A comparison of protein supplements and methods of feeding protein supplements to yearling steers wintered on bluestem pasture. - Smith, E.F.; Pickett, A.G. (Kansas Agricultural Experiment Station, 2012)
Good to choice quality yearling Hereford steers were used in this study which included four lots of 10 steers each. The objective was to determine the value of dry bluestem grass when supplemented with different proteins fed by various methods. All pastures used for winter grazing had been used the previous summer but were not closely grazed and dry grass was abundant. The steers were allowed from twelve to eighteen acres per head.
Keywords: Beef; Protein; Bluestem pasture; Gain